READING DURATION AND FINANCIAL LITERACY IN VOCATIONAL HIGH SCHOOL - Ayu Widya Ningsih; Afifa May Shara; Dinda Andriani; Kisno . (Jurnal Education and Development, 2021)
Minimum Competency Assessment is administered in 2021 to substitute National Examination to all students in Indonesia. However, it is estimated that the students, particularly from Vocational High Schools are not ready to face the assessment consisting of reading literacy, numeracy literacy, and financial literacy. This study aims to investigate the effect of the students’ duration in reading non-visual financial literacy texts on the students’ ability to read visual texts. Four limitation categories such as reading duration, reading content about financial literacy, reading non-visual text, and grade 10th of Vocational High School students were included in this study. A quantitative approach with correlational study was implemented and simple linear analysis was applied to examine the degree of relationship between the students’ duration in reading non-visual financial literacy texts and the students’ ability to read visual texts. An online survey and a test using Google Forms were carried out to obtain the students’ test result; the data was then analyzed using Microsoft Excel 2016. The simple linear regression test (Y = 0.32 + 1.68, with r = 0.93) indicated that the students’ duration in reading non-visual financial literacy texts had a very strong effect on their reading ability. The significance of this study is beneficial for preparing Vocational High School literacy especially relating financial skills and mathematical skills in facing minimum competency assessment or AKM which is commenced in 2021.